Psychological distress and post-traumatic growth in France during the COVID-19 pandemic: A mediation model of psychosocial safety climate as a determinant of work performance - Sandrin, Émilie; Brun, Jean-Pierre; Nguyen, Christophe; Biron, Caroline; Ivers, Hans (Frontiers in Psychology, 2022)
The psychosocial safety climate (PSC) reflects workers’ perceptions of senior management’s concern for mental health. Because the COVID-19 pandemic has exacerbated organizational issues, PSC could be a target for interventions attempting to preserve both the psychological health of employees and the economic health of companies. This study examines the direct and indirect relationships between PSC and work performance through two indicators of psychological health, psychological distress and post-traumatic growth, during a health crisis, i.e., prior to the second confinement in France. To this end, 2,004 participants from the French workforce completed a survey in October 2020. The results of mediation analyses indicate that PSC has a direct and positive influence on post-traumatic growth (PTG) and performance, as well as a direct negative influence on psychological distress. PSC also has an indirect positive influence on performance via psychological distress. Organizations that wish to jointly address mental health and performance at work would benefit from optimizing PSC.